Penggunaan Abu Kulit Kakao Sebagai Filler Pada Campuran Aspal AC-BC (Asphalt Concrete – Binder Course) Terhadap Nilai Marshall - Rani, Mifta Estika; Afilda, Salsabilah; Zainuddin, Zainuddin; Sari, Anggi Nidya (Universitas Batanghari Jambi, 2025)
Stone ash, lime, cement, or other materials can be used as fillers, which add strength and density to the asphalt concrete mixture (TotomiHardjo in Nawir, 2021). In this research, the filler used was ash from cocoa husk waste originating from cocoa farmers in Belitang, East Ogan Komering Ulu Regency, South Sumatra. The component of the cocoa plant that is widely used is the seed, while the husk is discarded as waste, so it needs to be managed further. Ash from cocoa husk contains carbon and silica (SiO2), ingredients needed for asphalt. By trying to utilize existing natural products, cocoa husk ash as a filler is expected to provide strength value to the asphalt mixture. This study used variations in asphalt content of 5.5%, 6%, and 6.5% with different variations in filler content, namely the ratio between cement (SM) and cocoa husk ash (ABK) of 6% SM: 0% ABK, 3% SM: 3% ABK, and 0% SM: 6% ABK. This study aims to determine the effect on the Marshall value of replacing filler with cocoa husk ash compared to cement. Based on the results of the Marshall test analysis, it is known that the filler composition that has the optimum value is a ratio of 0% SM to 6% ABK at an asphalt content of 6.5% with a stability value of 1759.79 kg, a flow value of 3.95 mm, a VIM value of 4.66%, a VFA value of 81.18%, a VMA value of 16.67%, and a Marshall Quotient of 444,78 kg/mm.